HUBUNGAN AKTIVITAS FISIK DAN POLA MAKAN DENGAN DISMENORE - Irma Amelia Puspitasari; Surdiniaty Ugelta; Hamidie Ronald Daniel Ray (PAIFORI, 2021)
The purpose of this study was to determine whether physical activity and dietary habits on dysmenorrhea in Kabupaten Bandung. The type of this research is quantitative. The population of this study is teenage girls in Kabupaten Bandung and the sample of this research amounted to 32 people with an age range of 16-24 years old. The data collection technique in this study is purposive sampling. The method that is used is descriptive with correlational design by using SPSS version 25. The output of this research shows that there is no significant relationship between physical activity (X1) and dysmenorrhea (Y), this is indicated by the value of sig. = 0,967 > 0,05. Besides that, the output of this research shows that there is no significant relationship between dietary habit (X2) and dysmenorrhea (Y), this is indicated by the value of sig. = 0,967 > 0,05. So, the results of this study contradict the research hypothesis.